(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
In this study a partial purification of laccase enzyme was carried out from rosemary. The purification steps included precipitation with acetone 75% as a first step, then purification using ion exchange chromatography on a DEAE-Sephadex column, followed by gel filtration chromatography using a Sephadex G100 column. Yield at the end of the purification steps was 54.14%, with a fold purification of 40.86 and a specific activity of 44.54 units/mg. The studied laccase showed a highest activity at pH 7, while its optimum temperature was 65 °C using 2-2`azino-bis (3ethl benzothiazottin 6 sulfonic acid) (ABTS) as a substrate. The results showed the thermal stability of the enzyme, where 55% of its activity remained after being incubated for an hour at a temperature of 75 °C, and laccase enzyme maintained more than 92% of its activity after being incubated for 24 hours at pH between (6-9). It should be noted that the above properties of the studied laccase enzyme give it great importance in various industrial applications.